ELECTROCHEMICAL BEHAVIOR OF GC, Pt AND Au ELECTRODES MODIFIED WITH THIN FILM OF COBALT HEXACYANOFERRATE (Journal of Sciences, Islamic Republic of Iran)
0A thin film of cobalt hexacyanoferrate (CoHCF), an analogue of mixed-valence Prussian blue, was deposited electrochemically on the glassy carbon, platinum and gold electrode surfaces in 0.5M KC1 solution. The electrochemical behavior of these modified electrodes show three couples of redox peaks by CV in a supporting electrolyte solution of 0.5M NaCl, whereas for Au modified electrode only one couple of redox peaks is observed because of self-oxidation of gold substrate at more positive potentials. The effect of various factors such as cations and anions of supporting electrolyte, solution pH, scan rate and the limit of sweeping potential on the CV response of modified electrodes was also studied. It was shown that the electrodeposited CoHCF film is stable for several days, whether stored at open circuit in a 0.5M KC1 or NaCl supporting electrolyte or in air